Foreign Debt: Causes and Theirs Impact on Economic Growth in Indonesia - Anggresta, Vella; Subiyantoro, Heru; Astuty, Pudji (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2024)
Research Originality: This study presents a new analysis of the primary determinants of Indonesia's foreign debt and its impact on economic growth over the 1992-2022 period, offering new insights into debt management strategies.Research Objectives: This study uses 31 years of time series data to analyze the main causes of Indonesia's foreign debt and its effect on economic growth.Research Methods: This research employs a quantitative approach with data analysis techniques, including classical assumptions, Ordinary Least Squares (OLS), simple linear regression, and hypothesis testing.Empirical Results: The results indicate that interest rates do not significantly affect Indonesia's foreign debt, while exchange rates and imports have substantial impacts. Additionally, a significant relationship between foreign debt and economic growth is confirmed.Implications: This study suggests that the Indonesian Government should adopt a multifaceted approach to managing foreign debt, including policies aimed at maintaining low interest rates, strengthening the rupiah, boosting exports, and enhancing government spending efficiency without excessive reliance on external borrowing.JEL Classification: F34, F43, H63, O11